Strategic Management in Addressing Hajj Cancellation Cases at the Ministry of Religious Affairs Office in Jember Regency - Eka, Eka Rahayu; Al Ahsani, Nasirudin (Maddah: Journal of Advanced Da'wah Management Research, 2025)
The implementation of Hajj is regulated by Law No. 8 of 2019 concerning the organization of Hajj and Umrah. The Ministry of Religious Affairs, as the institution responsible for managing and organizing Hajj and Umrah, faces challenges regarding the issuance of release permits. Jember Regency ranks among the highest in terms of Hajj cancellations. The purpose of this study is to determine: 1) Strategic management in addressing Hajj cancellation cases at the Ministry of Religious Affairs Office in Jember Regency, 2) Supporting and inhibiting factors in handling Hajj cancellation cases. This research adopts a qualitative approach, presented descriptively. The conclusions drawn from this study are as follows: The strategic management applied by the Hajj Management Unit (PHU) in addressing Hajj cancellations includes conducting educational programs for pilgrims, collaborating with KBIHU (Hajj and Umrah Guidance Institutions), KUA (Office of Religious Affairs), and socializing both directly at the location or through social media and Sharia Banks. The supporting factor in implementing strategic management to address cancellations is the cooperation between external and internal parties in the process of handling cancellations at the Ministry of Religious Affairs Office in Jember Regency. The inhibiting factors include miscommunication with prospective pilgrims and the involvement of certain travel agents who exploit the Hajj cancellation process to attract pilgrims, enticing them to perform Umrah instead.